Target Points in Trastuzumab Resistance. (26th February 2012) - Shojaei, Sahar; Gardaneh, Mossa; Rahimi Shamabadi, Abbas
Abstract : Epidermal growth factor (EGF) family of receptors is involved in cell growth and differentiation. The human EGF2 (HER2) lacks natural ligands, and correlation between HER2 levels and carcinogenesis makes the receptor an ideal candidate for targeted therapy in breast cancer. Trastuzumab is a humanized antibody applied against HER2-positive breast tumors in clinic. Metastatic tumors respond well to trastuzumab therapy for the first year, but development of antibody resistance helps the tumors to regrow allowing the disease to progress. Trastuzumab resistance is shaped via a range of intracellular signaling pathways that are interconnected and share in key effector molecules. Identification of a common node central to these resistance pathways could provide an ultimate solution for trastuzumab resistance in breast and other cancers.